THE STUDY OF RUNNING EFFICIENCY OF MORTAR PUMP BALL VALVES ACCORDING TO THE MOTION LAW OF PISTON - Коробко, Б. О.; Васильєв, Є. А. (Academic journal. Industrial Machine, Building Civil Engineering, 2017)
There has been examined the effect of changing the motion law of piston in a differential mortar pump on the amount of lossesof construction mortar mix of the injectionvalve which operates at closing. Keywords:differential mortar pump, piston, the law of motion, valve.